SEJARAH PERKEMBANGAN MUNCULNYA TAFSIR ISHARI DAN CONTOH-CONTOH PENAFSIRANNYA - Hermansyah (STAI DI AL-HIKMAH, 2022)
This paper analyzes the history of the development of Tafsir Ishari and some examples of its interpretation. This discussion of Tafsir and its interpretation is completed by qualitative research. The research data used are Tafsir Ishari, journals, books, Al-Qur'an, Hadith, and other relevant literature sources. The analysis in this paper uses textual analysis to make interpretations and conclude research results. This paper concludes that isyari interpretation as a style of interpretation actually has a strong basis for its emergence. Starting from the time of the prophet then to the generation of companions. Although this style of interpretation has not been recorded by the early generations. Only in the end, through gradual phases, did this style of isyari interpretation develop and become a style accepted by commentators. Of course, the commentators still provide quite strict requirements so that the isyari interpretation system does not experience deviations in interpreting the Qur'an.